Analysis of the Relationship between Type 2 Diabetes Mellitus and Chronic Kidney Failure Events at Royal Prima Hospital, Medan, in 2024 - Marito Arga Hasian Br Marpaung; Qori Fadillah; Irza Haicha Pratama (International Journal of Health and Pharmaceutical (IJHP), 2025)
Background: Type 2 diabetes mellitus (DMT2) is the leading cause of chronic renal failure (CCC) globally. Indonesia is projected to experience an increase in diabetes cases from 18.69 million in 2020 to 40.7 million in 2045. Objective: This research aims to analyze the relationship between type 2 diabetes mellitus and the incidence of chronic kidney failure at Royal Prima Hospital, Medan, in 2024. Methods: This cross-sectional study included 85 DMT2 patients selected using simple random sampling. Data collection used medical records, and statistical analysis using the Chi-Square test and prevalence ratio calculations at a 95% confidence level. Results: The study found a significant association between DMT2 and CKD (p = 0.018). The majority of female respondents (58.8%) were aged 45-60 (49.4%). Most cases of CKD in advanced stages: 23.5% stage 4 and 11.8% stage 5. DMT2 patients with complications of diabetic ketoacidosis and hyperosmolar hyperglycemic state had a 1.46 times higher risk of CKD. Conclusions: There is a significant association between type 2 diabetes mellitus and the incidence of chronic renal failure, so a systematic renal function screening program and comprehensive glycemic control education are needed